Research on Dynamic Performance of Locomotive Wheelset Driving Unitwith Gear Teeth Cracks - FAN Jiafeng; DENG Tiesong; LI Fuzhong; SU Zhaoyi (机车电传动)
In order to simulate the influences of gear teeth cracks on the dynamic performance of the wheelset driving system, withthe multi-body dynamic software SIMPACK, the vibration model of gear-pair meshing was established, which, meanwhile, was appliedto the dynamic model of locomotive wheelset driving unit. Moreover, without the inner FE (force element) gear-pair of SIMPACK, thegear-pair meshing model was realized through the methods of moved markers, function expressions, input functions and so on. The resultsshowed that the difference between gear-pair meshing model and FE gear-pair was smaller than 10 percent; The meshing vibration ofgear-pair performed the time-varying character of the meshing stiffness; The reference circle crack would have a time-domain impact onthe dynamic performance of wheelset driving unit; Through the basic frequency of the smaller gear which was exhibited by the wheelsetdriving unit, the impact could be detected through frequency-domain method when the crack reached to some certain depth (i.e. thestiffness reduced to some certain value). Therefore, such faults could be diagnosed by the frequency-domain analysis.